(untitled) (Journal of Pathology of Nepal, 2016)
Background: Pleural effusion is a common medical condition with many possible underlying etiologies. However, Tuberculosis is the most common cause of pleural effusion especially in countries like Nepal. Pleural uid lymphocytosis is seen in tuberculosis, malignancy and few auto-immune diseases. Adenosine Deaminase activity (ADA) level in tubercular pleural effusion is markedly increased compared to non-tubercular effusions. ADA estimation being a simple colorimetric method is suitable for the rapid diagnosis of tubercular effusion. This study aims to correlate the diagnostic ef cacy of ADA with the value of differential count (lymphocytosis) in establishing different etiology of pleural effusion. Materials and Methods: This is a cross sectional study of 50 cases with pleural effusion carried out in the department of Pathology, Green city hospital for the duration of Twenty one month’s dating from October 2014 to July 2016 AD. Results: Of all, tubercular pleural effusion accounted for 26%. ADA level was raised (≥40U/L) in 92% of Tubercular pleural effusion. The sensitivity and speci city of ADA alone to diagnose tubercular pleural effusion was 92% each and when lymphocytosis alone was considered sensitivity was 85% with speci city of 32% whereas the combined effect of both ADA with lymphocytosis was 100% (sensitivity) and 87% (speci city), 83% (positive predictive value) and 100% (negative predictive value) respectively with statistically signi cant p value (<0.05). Conclusion: We can conclude that the combination of pleural uid differential count (lymphocytosis >50%) and ADA level >40U/L provides with much more positive result than each component alone in differentiating tubercular effusion from other etiologies.